A mathematical model of an order management automated system within the process of production technological preparation in aviation enterprisers - P. E. Efimova (Моделирование и анализ информационных систем, 2010)
The article considers the analysis of an order management automated system used within the process of production technological preparation at the construction depart¬ment of the tool set design, its conceptual model using Petri nets is formulated, its mathematical model based on matrix method is worked out.